Going Green with Green HRM Practices – A Strategic Initiative for Reinvigorating Performance Optimization in Companies - Chakraborty, Debarun; Biswas, Wendrila (Prabandhan: Indian Journal of Management, 2020)
Organizations have developed a global identity with innovative human resource practices and operations which stand as a source of competitive advantage for the firms. With the advent of workforce diversity, globalization, technological incisiveness, and expeditious changes across companies, organizations are facing environmental challenges at work, which need to be addressed at large and managed as well. Green human resource management (GHRM) practices in organizations have become a key business strategy that play an active role in exploring the green facets of business. A significant difference in organizational performance is discerned when green human resource management techniques are implemented. In the present study, 264 respondents were selected (HR managers, HR officers, and HR executives of different companies). The findings of the present study revealed that Green Recruitment & Selection, Green Training, Green Performance Management, Green Rewards Management, and Green Employee Participation provided a way for green management perspective of the firms that promoted environmentalism and had a significant impact on the sustainability of the business. Such sustainable practices ingrained among employees a sense of commitment not only towards these environmental issues, but also towards the corporate mission statement of the organization, fulfilled its green objectives, and enhanced employees’ green performance of the job. The findings of the study highlighted that the green performance management (GPM) practices had a considerable impact on organizational performance. GPM practices enriched the behavioral and technical competencies of employees to align green tasks and goals that reinforced the company’s core values. The paper highlighted the significance of green performance management practices which had been instrumental in bringing out the competencies of employees, a natural environment in the workplace, improved employee implementation of green management principles, and corroborated strategic performance of the firms.